2023
DOI: 10.1038/s41598-023-30317-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in 2D p-type WSe2 transistors towards ultimate CMOS scaling

Abstract: This paper provides comprehensive experimental analysis relating to improvements in the two-dimensional (2D) p-type metal–oxide–semiconductor (PMOS) field effect transistors (FETs) by pure van der Waals (vdW) contacts on few-layer tungsten diselenide (WSe2) with high-k metal gate (HKMG) stacks. Our analysis shows that standard metallization techniques (e.g., e-beam evaporation at moderate pressure ~ 10–5 torr) results in significant Fermi-level pinning, but Schottky barrier heights (SBH) remain small (< 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…This can be attributed to the high e-beam power required for Pt evaporation, , resulting in severe damage to the WSe 2 . While previous reports suggest that Pt can be a suitable p-type contact metal for 2D TMD FETs if it is deposited with a low deposition rate in a high-vacuum environment, ,, further optimization of Pt deposition conditions (e.g., metal-to-substrate distance) for p-type FeFETs will be necessary in future work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This can be attributed to the high e-beam power required for Pt evaporation, , resulting in severe damage to the WSe 2 . While previous reports suggest that Pt can be a suitable p-type contact metal for 2D TMD FETs if it is deposited with a low deposition rate in a high-vacuum environment, ,, further optimization of Pt deposition conditions (e.g., metal-to-substrate distance) for p-type FeFETs will be necessary in future work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Among the various defects, antisite defects [14], chalcogen atom vacancies [15,16], and nitrogen/oxygen impurities [17] are noteworthy contributors to mid-gap states in monolayer TMDs. These mid-gap defects might effectively act as recombination centers or carrier traps under different conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, good contacts cannot be made to p ‐type devices and large variabilities are seen for n‐type contacts. [ 4–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, good contacts cannot be made to p-type devices and large variabilities are seen for n-type contacts. [4][5][6][7] Experiments have shown that degrees of hybridization and defect generation during the metallization process plays a critically important role in determining the contact resistance. [8][9][10][11][12] Specifically, mechanical transfer of metals results in van der Waals contacts with reduced pinning and enhanced performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation